2017
DOI: 10.1111/acv.12361
|View full text |Cite
|
Sign up to set email alerts
|

Habitat selection and range use of little owls in relation to habitat patterns at three spatial scales

Abstract: Understanding the rules of habitat selection and the individual behavioural routines in the home-range is crucial for developing evidence-based conservation action. We investigated habitat selection and range use of adult little owls Athene noctua in relation to landscape configuration, habitat structure and resource distribution. We determined the preference of habitat structures by VHF-telemetry. Large-and fine-scale distribution patterns of volesthe main prey during the breeding season were assessed by tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 36 publications
0
36
0
Order By: Relevance
“…Westerman et al 2003a ; Baraibar et al 2012 ; Fischer et al 2017 ). Rodent densities in crop fields are often relatively low (Aschwanden et al 2007 ; Fischer and Schröder 2014 ; Apolloni et al 2017 ) and a previous study found low predation rates by rodents (e.g. Baraibar et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Westerman et al 2003a ; Baraibar et al 2012 ; Fischer et al 2017 ). Rodent densities in crop fields are often relatively low (Aschwanden et al 2007 ; Fischer and Schröder 2014 ; Apolloni et al 2017 ) and a previous study found low predation rates by rodents (e.g. Baraibar et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…As it was already previously known, it hunts for a wide variety of prey due to its large distribution area and various hunting techniques (Mikkola 1983, Cramp 1985, Angelici et al 1997, Van Nieuwenhuyse et al 2008. This is well reflected in the prey composition of Little Owls of different geographical regions (Shehab et al 2004, Charter et al 2006, Kayahan & Tabur 2016, and in different habitats within the same geographical region (Van Nieuwenhuyse et al 2008, Apolloni et al 2018. The role of small mammals in the Southern European region is generally less important; however, vertebrates can be dominant in some Mediterranean regions (Goutner & Alivi zatos 2003); in Central Europe the proportion of small mammals is usually high (Zerunian et al 1982, Mánez 1983, Schönn et al 1991, Ille 1992, Genot & Van Nieuwenhuyse 2002, Gorzel & Grzywaczewski 2003, Tomé et al 2008, and the present study).…”
Section: Discussionmentioning
confidence: 98%
“…This negative tendency can be observed also in the case of farmland bird species in Hungary (Szép & Nagy 2006, Báldi & Batáry 2011, Szép et al 2012. Nevertheless, in addition to nesting-site availability, the trend of a given Little Owl population is closely related to the feeding possibilities and food availability (Génot & Van Nieuwenhuyse 2002, Thorup et al 2010, Apolloni et al 2018. In general, the effects of agricultural intensification may result in a decrease in the abundance of arthropods and small mammals (Morris 2000), which are the primary food sources for the Little Owl (Van Nieuwenhuyse et al 2008).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…S1). The study areas are characterized by a mosaic of intensively cultivated agricultural fields, sown leys, permanent meadows, vineyards and orchards (Grüebler et al 2014 ; Apolloni et al 2018 ). Whereas Germany and Switzerland were broadly inhabited by little owls in the middle of the last century, populations recently declined as they did across many parts of Europe with only a few breeding pairs left in Switzerland (Schaub et al 2006 ; Thorup et al 2010 ; Habel et al 2015 ).…”
Section: Methodsmentioning
confidence: 99%